STRATEGI KOMUNIKASI INTERPESONAL KARYAWAN BPJS KETENAGAKERJAAN DALAM MENINGKATKAN KEPERCAYAAN DAN LOYALITAS PESERTA BPJS - Epran Ari Pernando; Rina Febriana (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
PJS is the abbreviation of Social Security Administering Body. In Indonesia, there are several BPJS institutions that are responsible for administering social security programs, including: BPJS Health (Health Social Security Administering Agency): and BPJS Employment. This research uses a qualitative approach and case study method, data was obtained through in-depth interviews with BPJS Employment employees and direct observation at the South Sumatra Regional Office. To simplify the research process, of course, researchers also use several theories, including interpersonal theory and consistent loyalty theory. The results of the analysis show that BPJS Employment employees apply several effective interpersonal communication strategies to increase participant trust and loyalty. First, they emphasize the importance of an active and friendly physical presence in interacting with participants. These employees strive to give full attention to participants, listen carefully, and provide relevant responses to every question or problem raised by participants. BPJS Employment employees use language that is easy for participants to understand, avoiding the use of complicated technical terms. In conclusion, the interpersonal communication strategy used by BPJS Employment employees at the South Sumatra Regional Office has proven to be effective in increasing participant trust and loyalty. BPJS Employment employees have succeeded in creating good relationships with BPJS participants.